"'Bach, Please': Nashville bachelorette party culture's investments in white Southern femininity". Issue 1 (2nd January 2023) - King, Claire Sisco
ABSTRACT: In the 2010s, multiple media outlets declared Nashville an "It City." No longer simply the home of country music, Nashville became a popular tourist destination with particular appeal to white women bachelorettes. Nashville's bachelorette party culture encourages women to "celebrify" themselves by supporting scopic economies through public amenities and social media sharing—while simultaneously reinforcing white, Eurocentric, cisheterosexual beauty norms refracted through fantasies about Southern womanhood. This tourist industry, which has dramatically altered Nashville's public image, relies on and reaffirms centuries-old fantasies about white women that are designed to be detrimental, if not dangerous, to Black lives.